2017
DOI: 10.1016/j.plaphy.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence towards the involvement of nitric oxide in drought tolerance of sugarcane

Abstract: Exogenous supply of nitric oxide (NO) increases drought tolerance in sugarcane plants. However, little is known about the role of NO produced by plants under water deficit. The aim of this study was to test the hypothesis that drought-tolerance in sugarcane is associated with NO production and metabolism, with the more drought-tolerant genotype presenting higher NO accumulation in plant tissues. The sugarcane genotypes IACSP95-5000 (drought-tolerant) and IACSP97-7065 (drought-sensitive) were submitted to water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 41 publications
(37 reference statements)
1
15
0
1
Order By: Relevance
“…In this work, a commercial genotype of sugarcane from São Paulo State, in Brazil, was used to study the proteome of drought‐stressed sugarcane. Previous studies showed that the genotype used here had a higher capacity to accumulate biomass compared with other commercial varieties when exposed to drought …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this work, a commercial genotype of sugarcane from São Paulo State, in Brazil, was used to study the proteome of drought‐stressed sugarcane. Previous studies showed that the genotype used here had a higher capacity to accumulate biomass compared with other commercial varieties when exposed to drought …”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we used a highly productive commercial sugarcane cultivar (IACSP 95–5000), which has been characterized as drought‐tolerant with the aim to identify drought‐stress responsive proteins in the stems which are the major sinks of photosynthates used to produce the main products from sugarcane (ethanol, biomass, and sugar). These proteins are responsible for the control of metabolic pathways that affect directly the quality and yield of sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased NO levels prevent stomatal closure caused by SNP [34], so adding NO and its interaction can increase drought tolerance. Furthermore, [35] recently reported that the exogenous supply of NO enhances drought tolerance in sugarcane plants.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that NO and Ca 2+ , as plant signaling regulators, may work together in response to abiotic stresses has been reported ( Silveira et al, 2017 ). In the present study, when Ca 2+ chelators, Ca 2+ channel inhibitors, and CaM antagonists were applied, the promoting effects of NO on vase life was blocked.…”
Section: Discussionmentioning
confidence: 99%